The Application of Office Automation Software in Management Work - Li, Cong (Journal of Theory and Practice of Social Science, 2023)
With the development of business and the progress of science and technology, the management consciousness and management environment are quietly changing, the traditional management structure has been broken, gradually to the flat, systematic management mode transition, so that the requirements of management hardware and software facilities are constantly improving. The use of office automation software can not only meet the needs of processing a large amount of information, but also improve the quality and efficiency of management, reduce the workload of managers, realize the automation and standardization of company management, and gradually create more wealth and benefits with knowledge. Therefore, this paper analyzes the application of office automation software in management.